posted by krista .
show that k(x)= (5x^3) + (5/x^3) - x- (1/x)
^ sorry didn't finish: show that k(x)= k(1/x)
let me rewrite k(x)
k(x) = 5(x^3) + 5(1/x^3) - x/1 - 1/x
it should be intuitively obvious that
k(x) = k(1/x)
yea i realize that but the question says "show" that they equal each other. im thinking possibly by some sort of identity or something.
sub 1/x for x
k(1/x) = 5(1/x^3) + 5/(1/x^3) - 1/x - 1/(1/x)
= 5/x^3 + 5x^3 - 1/x - x
= the original k(x) , just the order of writing down the terms has changed.
ohh i see duh!! lol thanks =)